Deceptive Design and Ongoing Consent in Privacy Law - Wiener, Jeremy (Ottawa Law Review / Revue de droit d’Ottawa, 2021)
The Consumer Privacy Protection Act is the first proposed privacy statute to regulate the deceptive privacy practices that undermine individuals’ right to consent. The problem is that there is no framework for determining how the Act might actually apply. This article resolves the issue by filling three gaps in the literature.First, it categorizes different types of deception according to privacy law’s notice-and-choice framework, providing a method of analysis for scholars and regulators. It then concretizes the framework by comparatively surveying investigations led by the United States’ Federal Trade Commission and Office of the Privacy Commissioner of Canada (OPC). This will shed light on how the Act can be interpreted, and will constitute a comprehensive survey of a thematic area of OPC investigations.Finally, the article explores whether the Act defines consent as an act of ongoing agency, which would protect peoples’ privacy by covering deception that occurs not only at “I agree moments,” but also beyond “I agree moments.” Ultimately, this article guides judges and regulators in enforcing the Act, assists policy-makers in developing more statutory provisions that regulate deceptive privacy practices, and contributes to doctrine by filling the aforementioned gaps.